Spol in rabe intimnih tehnologij - Pušnik, Maruša (Teorija in praksa, 2017)
The paper is based on an ethnographic study of gender differentiation of young audiences of new media in the everyday life context. We assume that social media should be considered as genres with a generic mise-en-scene and ideology which frame specific forms of gender-specific sociability and practices of distinction. We conclude that in the modern conditions of the naturalisation of social media, "constant presence" and "permanent on-line connectedness", the traditional differences between male and female users/producers are largely being reproduced. Women are more likely to use social platforms for social and emotional integration and for the construction of consumer subjectivity, while men use such media forms for more instrumental purposes and to create an alternative reality through computer games and sport. In this way, the gender dichotomy between the "inwardly-oriented" tastes of women and "outwardly-oriented" tastes of men, that exists in intersection with class affiliation, and are characteristic of television consumption, is being reproduced in the digital culture.
Keywords: digitalna kultura; Družbeni mediji; Sex differentiation; Social media; Sociologija vsakdanjega življenja; Sociology of everyday life; Spolna diferenciacija